Reform of the Fund's Policy on Poverty Reduction Strategies in Fund Engagement with Low-Income Countries : Proposals. (Policy Papers; Policy Paper ;, 2015)
Poverty reduction strategies (PRS) are central to Fund-supported economic and financial programs in low-income countries (LICs). The joint IMF-World Bank's Heavily Indebted Poor Country (HIPC) Initiative introduced the PRS approach and established documentation requirements centered on the Poverty Reduction Strategy Paper (PRSP). The PRS approach has also been a cornerstone for the Fund's concessional financing, currently the Extended Credit Facility (ECF), and has been extended to the Policy Support Instruments (PSI), the non-financing instrument for LICs, with PRS documentation serving as the operational framework for development of strategies to promote growth and reduce poverty under Fund-supported programs.